2018
DOI: 10.1002/eqe.3052
|View full text |Cite
|
Sign up to set email alerts
|

Seismic hazard in Buenos Aires, Argentina: A preliminary study on the effects of long‐distance earthquakes on tall buildings

Abstract: Summary The 2015 Illapel earthquake produced self‐evacuation of tall buildings in the city of Buenos Aires, Argentina, located 1280 km away from the epicenter. The ground motions in Buenos Aires due to the main event (Mw 8.3) and its aftershocks were registered by a new seismometer. The data collected allowed to estimate the maximum story drift ratios and top floor accelerations for tall buildings in Buenos Aires. The similarities between the response spectra and the Fourier amplitude spectra for the mainshock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As further noted in Bertero et al (2018), regarding these distantly generated long period effects in Buenos Aires -where firm soil is found in the upper layers: site "amplification" resulting from polarization of seismic wave motion in the horizontal plane is produced because of the large depth of soil deposits.…”
Section: Time (S)mentioning
confidence: 87%
See 2 more Smart Citations
“…As further noted in Bertero et al (2018), regarding these distantly generated long period effects in Buenos Aires -where firm soil is found in the upper layers: site "amplification" resulting from polarization of seismic wave motion in the horizontal plane is produced because of the large depth of soil deposits.…”
Section: Time (S)mentioning
confidence: 87%
“…As shown in Fig. 3 from Bertero et al (2018), tall buildings in Buenos Aires (1280 km away from the epicenter), although a great distance away from the 2015 Mw 8.3 Illapel, Chile earthquake, experienced horizontal acceleration time-series of motion that were significantly higher than the "motion perception threshold" limit for wind-induced vibrations as specified in ISO 10137 ( 2007) for human comfort, productivity and well-beingbecause motions at frequencies less than 1 Hz can provoke fear, discomfort and symptoms of motion sickness in buildings occupants.…”
Section: Magnitude Power Broadcastmentioning
confidence: 93%
See 1 more Smart Citation
“…In a recent study of the elastic response of tall buildings to Rayleigh waves, we pointed the vulnerability of such long‐period structures to basin‐induced surface waves. Reinforcing evidence supporting such a conclusion (among other observations summarized in our previous study) may be found in Bertero et al (2018) who investigated the response of a number of tall buildings in Buenos Aires, Argentina, which were excited by the seismic motions (Rayleigh wave) generated by the M w 8.3 Illapel, Chile earthquake, 1280 km away.…”
Section: Introductionmentioning
confidence: 99%